Fuzzy Linear Automata and Some Equivalences - Costa, Valdigleis S.; Bedregal, Benjamin (Trends in Computational and Applied Mathematics, 2018)
In this paper, we present two new normal forms for fuzzy linear grammars that  preserving language. In addition, we introduce two new classes of fuzzy machines, Fuzzy Linear Automata (FLA) and Fuzzy Nondeterministic 2-Tape Automata (2-FNA), we show the equivalence between them and also show that the class of fuzzy languages recognized by these machines is exactly the class of fuzzy linear languages, i.e., FLA and 2-DNA are recognized machines for class of fuzzy linear languages.